Cukilan Lagu Sunda Penyemangat Perjuangan pada Masa Perang Kemerdekaan - Komala, Icuh (LP2M ISBI Bandung, 2021)
Basically, during the struggle for Indonesian independence, not only the politicians and the military were involved (1945-1949), but the entire Indonesian community, including the artists in Sundanese musicals. The purpose of writing this article aims to reveal the participation of Sundanese musicians during the Independence period. It was pretty significant considering the role of Sundanese music in the struggle for independence is still little shown in Indonesian history. The method used is the historical method which includes the stages of heuristics, criticism, interpretation, and historiography. The result was found in musical works that ignited the spirit of the struggle for independence, such as Halo-Halo Bandung, Mars Siliwangi, Karatagan Pahlawan, and Dikantun Tugas.